Samowystarczalność energetyczna na szczeblu lokalnym - Godlewska, Joanna (Energy Self-Sufficiency on the Local Level, 2009)
Ensuring energy safety is one of the main problems occurring on the level of the whole country as well as on the local one. Climate protection is another priority goal of contemporary ecological policy that requires special attention. The exploitation of renewable energy sources on the local level is one of important solutions providing potential for an increase of energetic safety and climate protection as well. It also brings economic and other advantages. Another solution is energy saving by means of an increase of the efficiency of energy resources consumption. It can be achieved in technological respect owing to the cogeneration utilizing. Practical possibility of using renewable energy resources and cogeneration processes in one area can be achieved by the creation of Ecological Energy Park.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 82-90